2016
DOI: 10.1021/acsnano.6b04904
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Depleted Monolayered Molybdenum Disulfide Nanocrystals for Superelectrochemical Hydrogen Evolution Reaction

Abstract: ABSTRACT. Catalytically-driven electrochemical hydrogen evolution reaction (HER) of monolayered molybdenum sulfide (MoS 2 ) is usually highly supressed by the scarcity of edges and low electrical conductivity. Here, we show how the catalytic performance of MoS 2 monolayers can be improved dramatically by catalyst size reduction and surface sulphur (S)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
164
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(182 citation statements)
references
References 37 publications
1
164
0
Order By: Relevance
“…In addition, the Ajayan group demonstrated that oxygen plasma treatment and H 2 annealing introduced additional active sites within the MoS 2 monolayer, significantly improving the HER activity [44]. Recently, more rational and controllable defect modulation has been reported through combined experimental and theoretical studies [4547]. Allwood and co-workers prepared MoS 2 nanocrystals and activated the Mo atoms in the basal surface of MoS 2 nanocrystals by S depletion [45], with the resulting activated MoS 2 exhibiting an very high HER performance (~150 mV at −10 mA cm −2 and a Tafel slope of ~29 mV dec −1 ).…”
Section: Synthetic Strategies For Increasing Active Site Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Ajayan group demonstrated that oxygen plasma treatment and H 2 annealing introduced additional active sites within the MoS 2 monolayer, significantly improving the HER activity [44]. Recently, more rational and controllable defect modulation has been reported through combined experimental and theoretical studies [4547]. Allwood and co-workers prepared MoS 2 nanocrystals and activated the Mo atoms in the basal surface of MoS 2 nanocrystals by S depletion [45], with the resulting activated MoS 2 exhibiting an very high HER performance (~150 mV at −10 mA cm −2 and a Tafel slope of ~29 mV dec −1 ).…”
Section: Synthetic Strategies For Increasing Active Site Densitiesmentioning
confidence: 99%
“…Recently, more rational and controllable defect modulation has been reported through combined experimental and theoretical studies [4547]. Allwood and co-workers prepared MoS 2 nanocrystals and activated the Mo atoms in the basal surface of MoS 2 nanocrystals by S depletion [45], with the resulting activated MoS 2 exhibiting an very high HER performance (~150 mV at −10 mA cm −2 and a Tafel slope of ~29 mV dec −1 ). Cao and co-workers also verified the importance of S vacancies on the catalytic activity for the HER [46], estimating the intrinsic TOFs of the edge sites, S vacancies, and grain boundaries as approximately 7.5, 3.2, and 0.1 s −1 , respectively.…”
Section: Synthetic Strategies For Increasing Active Site Densitiesmentioning
confidence: 99%
“…Therefore, the more precise the control over these characteristics, the better would the 0D TMDs' overall functionalities. So far, a range of approaches have been utilized for preparation of 0D TMDs and those synthetic routes can be classified as top‐down and bottom‐up approaches . Top‐down synthesis approaches are based on exfoliation of their bulk crystals or etching of larger 2D morphologies, whereas bottom‐up approaches are conducted through a range of synthesis routes with diverse kinds of transition metal and chalcogenide precursors.…”
Section: Synthesismentioning
confidence: 99%
“…Bulk TMDs crystals were intercalated with K atoms between those covalently bonded sheets. Subsequently, the reaction between K atoms and ethanol/H 2 O mixture produce H 2 gases, inducing successful separation of 0D TMDs (Figure b) . Otherwise, starting TMDs materials ultimately determine the eventual morphologies of TMDs nanostructures.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation